Sensory diversity of a traditional Slovenian dry-cured sausages (Suha klobasa) - Demšar, Lea; Lesar, David; Lušnic Polak, Mateja; Polak, Tomaž (2019)
Suha klobasa is a popular dry-cured sausage that is produced practically everywhere in Slovenia. The aim of this study was to investigate the main characteristics of Suha klobasa produced by different manufacturers across five different informal regions of Slovenia. Products from 31 producers, as households (11), small workshops (15) or industrial plants (3) were analysed for pH value, moisture, protein, fat, and ash, as well as for their sensory parameters, according to assessments of four profiles: appearance, texture, smell and aroma. Technological production procedures were evaluated on the basis of a survey. In average Slovenian Suha klobasa pork is used, also Suha klobasa is characterized by slow ripening and smoking or without smoking but overgrown with mould. It is always filled in a small diameter casings (32-34 mm) of the pig small intestine or permeable casings, formed in two equal-length-halves and on one side (open side) looped around, often with a wooden stick. According to the regions of Slovenia, several types of Suha klobasa can be distinguish that are defined by sausage length and surface colour, mosaic and porousness on the one hand, and acid, smoke, mould, rancid smell/aroma on the other. Suha klobasa originated from different manufacturing practices differ in visual characteristics of product (size, equality and mould), in cross-section (mosaic, porousness and glassines), and texture (hardness, toughness and integrity) but not in olfactory and aroma profile.
Suha klobasa je popularna trajna kobasica koja se proizvodi gotovo svuda u Sloveniji. Cilj ovog rada bio je istražiti glavne značajke suhe klobase različitih proizvođača iz pet neslužbenih regija Slovenije. Proizvodi 31 proizvođača, odnosno domaćinstva (11), manjih gospodarstva (15) i industrijskih postrojenja (3), analizirani su na pH, vlagu, bjelančevine, masti i pepeo te senzorska svojstva, prema procjenama četiri značajke: izgled, tekstura, miris i aroma. Tehnološki proizvodni postupci ocjenjivani su na temelju ankete. Za suhu klobasu najčešće se upotrebljava svinjetina, a obilježavaju je sporo zrenje i dimljenje ili uporaba plemenitih plijesni bez dimljenja. Uvijek se puni u ovitke od svinjskog tankog crijeva ili propusne ovitke malog promjera (32-34 mm), a oblikuje se u dvije polovice jednake duljine koje su na jednoj strani (otvorena strana) presavijene, najčešće uporabom drvenog štapa. Ovisno o regiji Slovenije, možemo razlikovati nekoliko vrsta suhe klobase koje su, s jedne strane, određene duljinom kobasice i bojom površine, mozaikom i poroznošću te, s druge strane, kiselošću, dimom, plijesni i neugodnim mirisom/aromom. Iako se suhe klobase koje potječu iz različitih proizvodnih praksi razlikuju po vizualnim značajkama proizvoda (veličina, ujednačenost oblika i prisustvo plijesni), presjeku (mozaik, poroznost i sjaj) i teksturi (tvrdoća, žilavost i cjelovitost), njihovi se olfaktorni i aromatični profili ne razlikuju.
Die Trockenwurst ist eine bekannte Dauerwurst, die fast überall in Slowenien hergestellt wird. In dieser Arbeit wurden die wichtigsten Eigenschaften der Trockenwurst von diversen Herstellern aus fünf nicht offiziellen Regionen Sloweniens untersucht. Die Produkte von 31 Herstellern, bzw. landwirtschaftlichen Haushalten (11), kleineren Bauernhöfen (15) und Industrieanlagen (3) wurden in Bezug auf den pHWert, die Feuchtigkeit, den Eiweiß-, Fett- und Ascheanteil sowie sensoriche Eigenschaften anhand einer Bewertung von 4 Merkmalen untersucht: Aussehen, Textur, Geruch und Aroma. Die technologischen Herstellungsverfahren wurden anhand einer Umfrage bewertet. Für die Herstellung der Trockenwurst wird am häufigsten Schweinefleisch verwendet. Das Herstellungsverfahren kennzeichnen eine langsame Reifung und Trocknung sowie der Einsatz von Edelschimmel ohne Räucherung. Sie wird immer in ein dünnes Schweinedarm oder durchlässige Därme mit einem geringen Durchmesser (32-34 mm) abgefüllt. Sie wird in zwei gleich lange Hälften geformt, die an einer Seite (der offenen Seite) gefaltet werden, meistens durch Einsatz eines Holzstocks. Abhängig von der Region Sloweniens können wir mehrere Sorten der Trockenwurst unterscheiden, die auf der einen Seite durch die Länge der Wurst und die Farbe der Oberfläche, das Mosaik und die Porosität bestimmt werden und auf der anderen Seite durch den Säuregrad, Rauch, Schimmel und unangenehmen Geruch/Aroma. Obwohl die Trockenwürste, die aus unterschiedlichen Herstellungspraxen stammen, nach ihren visuellen Eigenschaften (Größe, ausgewogene Form und Anwesenheit von Schimmel), dem Durchmesser (Mosaik, Porosität und Glanz) und der Textur (Härte, Zähigkeit und Kompaktheit) unterschieden werden, gibt es zwischen ihren olfaktorischen und aromatischen Profilen keine Unterschiede.
El salchichón es el embutido curado popular producido casi en todas partes de Eslovenia. El fin de este trabajo fue investigar las características principales del salchichón suha klobasa de diferentes productores de cinco regiones no oficiales de Eslovenia. En los productos de 31 productores, es decir de hogares (11), granjas pequeñas (15) y plantas industriales (3), fueron analizados los pH, la humedad, las proteínas, la grasa, las cenizas y las características sensoriales, según las evaluaciones de cuatro características: la apariencia, la textura, el olor y el aroma. Los procesos tecnológicos de producción fueron evaluados a base de la encuesta. Para el salchichión suha klobasa se usa más a menudo la carne de cerdo, caracterizado por la maduración y el ahumado lentos o por el uso de las moldes nobles sin el ahumado. Siempre tiene el recubrimiento de la tripa del intestino delgado porcino o los recubrimientos permeables del diámetro pequeño (32-34 mm), es formada de dos partes de longitudes similares, doblada por un lado (la parte abierta) normalmente usando un palo de madera. Dependiendo de la región de Eslovenia, es posible distinguir varios tipos de la salchicha suha klobasa, que están determinados por la longitud y el color de la superficie, el mosaico y la porosidad por un lado y por la acidez, el humo, las moldes y el olor/aroma desagradable por otro lado. Aunque las salchichas de diferentes prácticas de producción se diferencian por las características visuales del producto (el tamaño, la uniformidad de la forma y la presencia de moldes), el corte transversal (mosaico, porosidad y el brillo), y la textura (la dureza, a resistencia y la integridad), sus perfiles olfativos y aromáticos no se distinguen.
La suha klobasa è una salsiccia secca molto popolare la cui produzione è largamente diffusa in Slovenia. La finalità di questa ricerca consiste nell’indagare le principali caratteristiche delle suhe klobase di diversi produttori provenienti da cinque regioni “ufficiose” della Slovenia. I prodotti di 31 produttori, 11 provenienti da aziende a conduzione familiare, 15 da piccoli stabilimenti e 3 da grandi impianti industriali sono stati analizzati riguardo al pH, all’umidità, alle proteine, ai grassi e alle ceneri e riguardo alle proprietà sensoriali secondo la valutazione di quattro caratteristiche: aspetto, consistenza, odore e aroma. I processi tecnologici di produzione sono stati valutati sulla base di un questionario. Per la produzione della suha klobasa prevale l’uso della carne suina. Il suo processo produttivo è caratterizzato da una lenta stagionatura e dall’affumicatura oppure dall’uso di muffe nobili senza affumicatura. Per fare la salsiccia si usa sempre il budello naturale suino (intestino tenue) o un budello sintetico permeabile di piccolo diametro (32-34 mm) che si modella in due metà d’identica lunghezza, incurvate nella parte aperta di solito con l’uso di una bastone di legno. A seconda della regione slovena di provenienza, possiamo distinguere differenti tipologie di suha klobasa, alcune caratterizzate dalla lunghezza della salsiccia e dal colore della sua superficie, dal tipico mosaico e dalla porosità, altre caratterizzate dall’acidità, dall’affumicatura, dalla muffa e dal profumo/aroma sgradevole. Sebbene le suhe klobase derivanti da differenti prassi produttive si differenzino per le peculiarità visive del prodotto (grandezza, uniformità della forma e presenza di muffe), per la sezione al taglio (mosaico, porosità e lucentezza) e per la consistenza (durezza, tigliosità e integrità), i loro profili olfattivi e aromatici non si differenziano.
Bibliografija: 21 jed.
Abstract ; Sažetak ; Zusammenfassung ; Resumen ; Riassunto.
Keywords: Mesni proizvodi -- Tradicionalni proizvodi -- Kobasice -- Trajne kobasice -- Proizvodne prakse -- Senzorska svojstva; Slovenija